Biharmonic Curves according to Parallel Transport Frame in E4 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study biharmonic curves according to parallel transport frame in E-4. We give some characterizations for curvatures of a biharmonic curve in E-4
Keywords: Heisenberg group; fluid flow; biharmonic curve; parallel transport frame